Effects heat stress in summer on some physiological characters in Iraqi indigenous goets - Ola Hussen Ali; Salih Hassan Al- Azzawi; Raaed Ibrahim Khalil (Zien Journals, 2022)
This study was conducted in the animal field of the Department of Animal Production - College of Agriculture - University of Diyala.. The study included 47 local female goats in the Baquba region of Diyala Governorate, located between two latitudes (3, 33ˉ and 35.6ˉ) north and (44.22ˉ and 45.56ˉ) east longitudes. This study was carried out in the summer(through Auguast mounth), i.e., during the presence of heat stress to know the effect of hair color, presence of horns ,Watals , and pregnancy on hematological characteristics PCV, volume of compacted blood cells, Hb, hemoglobin concentration and RBC calculation Red blood cell count and WBC count white blood cell count and each of the ALT enzyme, the amino group transporter enzyme, and the ALP enzyme, the alkaline phosphatase enzyme, heat stress has a significant impact on the homatogical traits of goats and that this effect is negative and the goats can adapt physiologically, including blood traits and enzymes, which are considered as an indicator of their range The animal was subjected to stress and there was no study stating the effect of ratchets or horns on blood characteristics, where the results of the analysis of variance showed a significant effect of these factors on WBC, RBC and ALT. As for HP, there was an effect of black and white color in casting In the evening, this may be due to the high humidity in the morning. In addition to this, there was a significant effect of black and white color, and when the horns were present on the ALP enzyme, it was higher in the morning than in the evening
Keywords: Heat Stress; Physiological; Raqi Goet